Analisis Celebrity Endorsment, Variasi Produk, Brand Image terhadap Keputusan Pembelian Produk Rabbani - Cahya, Fadlilah Mutia; Wulan, Ida Aryati Dyah Putnomo; Damayanti, Ratna (Jurnal Ilmu Manajemen, 2019)
The point of research to analyze a affect celebrity endorsement, product variation and brand image simultaneously, partially to the purchasing decisions Rabbani product in Surakarta. The research using quantitative methods. Used 100 respondents to the sample and the sampling technique was done by purposive sampling. The population is all consumers of Rabbani products in the city of Surakarta. Data collection is done by documentation, questionnaires, observation and data analysis techniques using instrument testing, classic assumption test, linear regression, F test, t test, determination (R2). Results F test is celebrity endorsement, product variation and brand image simultaneously and significantly influence the purchasing decisions of Rabbani products in Surakarta city with Fcount 47.681> Ftable 2.70 and significant value 0.000 <0.05. Celebrity endorsement, product variation and brand image partially a significant and positive effect purchase decisions of Rabbani products in Surakarta.